2015
DOI: 10.1007/s11224-015-0642-4
|View full text |Cite
|
Sign up to set email alerts
|

Structural significance of modified nucleoside 5-taurinomethyl-2-thiouridine, τm5s2U, found at ‘wobble’ position in anticodon loop of human mitochondrial tRNALys

Abstract: The myoclonus epilepsy associated with ragged-red fibers (MERRF) is a mitochondrial encephalomyopathic disease caused due to the lack of hypermodified nucleoside 5-taurinomethyl-2-thiouridine at 'wobble' 34th position in the anticodon loop of human mitochondrial tRNA Lys . Understanding the structural significance of sm 5 s 2 U might be helpful to get more information about the MERRF disease in detail at the atomic level. Hence, conformational preferences of hypermodified nucleoside 5-taurinomethyl-2-thiouridi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 75 publications
2
4
0
Order By: Relevance
“…In the context of ASL tRNA Leu , it has been observed that τm 5 U 34 side chain also interacts with the ribose ring of U 33 viz . O2' 33 …HN(8) 34 ( Fig 2E ) and O3' 33 …HN(8) 34 ( Fig 2F ), which could be helpful to maintain ‘anti’ conformation of glycosyl torsion angle as found in previous studies [ 13 14 ]. These hydrogen bonding interactions might be useful to retain the proper orientation of τm 5 U 34 side chain.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…In the context of ASL tRNA Leu , it has been observed that τm 5 U 34 side chain also interacts with the ribose ring of U 33 viz . O2' 33 …HN(8) 34 ( Fig 2E ) and O3' 33 …HN(8) 34 ( Fig 2F ), which could be helpful to maintain ‘anti’ conformation of glycosyl torsion angle as found in previous studies [ 13 14 ]. These hydrogen bonding interactions might be useful to retain the proper orientation of τm 5 U 34 side chain.…”
Section: Resultssupporting
confidence: 63%
“…The hydrogen bonding interaction, O4' 34 …HC(6) 34 (Fig 2A) between ribose ring and τm 5 U 34 base has been found stable throughout MD simulation, whereas the interaction, O5' 34 …HC(6) 34 (Fig 2B) was found disturbed. These interactions might help to maintain the ‘anti’ conformation of glycosyl torsion angle ‘χ’, as found in earlier studies [1314]. The hydrogen bonding interaction, O1P 34 …HC(10) 34 (Fig 2C) between phosphate backbone and τm 5 U 34 side chain assists to retain ‘anti’ conformation of glycosyl torsion angle.…”
Section: Resultssupporting
confidence: 59%
“…Thus, the D-loop is involved in stabilization of the 3D structure of the tRNA molecule. The D-loop structure is also essential for recognition of the tRNA molecule by aminoacyl tRNA synthetases. , Similarly, the importance of the anticodon loop and anticodon stem loop has been well documented in previous reports. , Hence, the stability of these component domains was individually assessed to check for local structural changes with the help of parameters such as the RMSD or structural visualization.…”
Section: Resultsmentioning
confidence: 91%
“…42,43 Similarly, the importance of the anticodon loop and anticodon stem loop has been well documented in previous reports. 13,17 Hence, the stability of these component domains was individually assessed to check for local structural changes with the help of parameters such as the RMSD or structural visualization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation